“I am Girl. Hear me Roar”: Girlpower and Postfeminism in Chick lit jr. Novels - Nilson, Maria (Academic Quarter | Akademisk kvarter, 2013)
The article focuses on an example of chick lit jr., Meg Cabot’s Airhead-trilogy, and how feminism, postfeminism and girlpower are discussed in this text. The novels portray a conflict between the generations, where the daughter rejects her mother’s version of feminism. There is an interesting ambiguity in the text concerning feminist ideals which makes Cabot’s novels, along with many other examples of chick lit jr., difficult to define. But even if there’s a remnant of feminism in these novels, that version of feminism stays on the individual plane and never influences society as a whole.